The tissue-specific effects of different 17β-estradiol doses reveal the key sensitizing role of AF1 domain in ERα activity. (5th April 2020) - Fontaine, Coralie; Buscato, Melissa; Vinel, Alexia; Giton, Frank; Raymond-Letron, Isabelle; Kim, Sung Hoon; Katzenellenbogen, Benita S.; Katzenellenbogen, John A.; Gourdy, Pierre; Milon, Alain; Flouriot, Gilles; Ohlsson, Claes; et al.
Abstract: 17β-Estradiol (E2) action can be mediated by the full-length estrogen receptor alpha (ERα66), and also by the AF1 domain-deficient ERα (ERα46) isoform, but their respective sensitivity to E2 is essentially unknown. We first performed a dose response study using subcutaneous home-made pellets mimicking either metestrus, proestrus or a pharmacological doses of E2, which resulted in plasma concentrations around 3, 30 and 600 pM, respectively. Analysis of the uterus, vagina and bone after chronic exposure to E2 demonstrated dose-dependent effects, with a maximal response reached at the proestrus-dose in wild type mice expressing mainly ERα66. In contrast, in transgenic mice harbouring only an ERα deleted in AF1, these effects of E2 were either strongly shifted rightward (10–100-fold) and/or attenuated, depending on the tissue studied. Finally, experiments in different cell lines transfected with ERα66 or ERα46 also delineated varying profiles of ERα AF1 sensitivity to E2. Altogether, this work emphasizes the importance of dose in the tissue-specific actions of E2 and demonstrates the key sensitizing role of AF1 in ERα activity. Highlights: Some biological response to E2 displays biphasic dose relationship. ERαAF1 plays a key sensitizing role in ERα activity. Differences and even contradictory conclusions could be explained by differences of E2 doses.